2021
DOI: 10.1177/21674795211003524
|View full text |Cite
|
Sign up to set email alerts
|

One and Done: The Long Eclipse of Women’s Televised Sports, 1989–2019

Abstract: For 3 decades we have tracked and analyzed the quantity and quality of coverage of women’s and men’s sports in televised news and highlights shows. In this paper, we report on our most recent iteration of the longitudinal study, which now includes an examination of online sports newsletters and social media. The study reveals little change in the quantitative apportionment of coverage of women’s and men’s sports over the past 30 years. Men’s sports—especially the “Big Three” of basketball, football and basebal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 44 publications
3
57
0
1
Order By: Relevance
“…In addition to establishing a fraught context for the full inclusion of transgender athletes, segregation enables unequal support for and value of women's sports. Sports for girls and women remain severely under-funded (Staurowsky et al 2020), opportunities for women in coaching and athletic leadership have substantially decreased in the past decades (Sabo et al 2016;Whisenant 2003), female athletes remain vulnerable to sexual harassment and abuse (Macur and Levenson 2021;Novkov 2019), media coverage of women's sports falls well below that of men's (Cooky et al 2021), and when women athletes are covered it is more likely to be through sexualizing frames (Musto et al 2017;Musto and McGann 2016).…”
Section: Sports Bodies and Title IXmentioning
confidence: 99%
“…In addition to establishing a fraught context for the full inclusion of transgender athletes, segregation enables unequal support for and value of women's sports. Sports for girls and women remain severely under-funded (Staurowsky et al 2020), opportunities for women in coaching and athletic leadership have substantially decreased in the past decades (Sabo et al 2016;Whisenant 2003), female athletes remain vulnerable to sexual harassment and abuse (Macur and Levenson 2021;Novkov 2019), media coverage of women's sports falls well below that of men's (Cooky et al 2021), and when women athletes are covered it is more likely to be through sexualizing frames (Musto et al 2017;Musto and McGann 2016).…”
Section: Sports Bodies and Title IXmentioning
confidence: 99%
“…For decades, scholarly research has deeply discussed the long-standing minimisation of sportswomen in day-to-day media coverage, highlighting that such underrepresentation is a consequence of cultural male hegemony in the sports world (Hardin, Dodd and Lauffer, 2006;Schell and Rodriguez, 2000). Across media platforms, the resulting coverage of leading female athletes and teams is still regarded as marginal compared to the frequency of appearances of their male counterparts (Coche, 2015;Cooky et al, 2021;Schoch, 2020). This gendered imbalance in the sports agenda is particularly important because it reinforces old cultural and androcentric stereotypes and acts as a barrier to promoting female role models in society (O'Neill and Mulready, 2015).…”
Section: The Gendered Sports Coveragementioning
confidence: 99%
“…Studies conducted over the last 30 years have consistently found the representation of women working in sports newsrooms is close to 10% (Henningham, 1995 ; Whiteside and Hardin, 2006 ; Nicholson et al, 2011 ), while women's sports coverage accounts for <10% (Lumby et al, 2014 ; Cooky et al, 2015 , 2021 ). Further, when women's sport is covered, rather than being prioritized, it is generally treated as secondary, or peripheral to men's sport.…”
Section: Literature Reviewmentioning
confidence: 99%